Comparison of the Knowledge and Practices in Medicine Dispensing between Retail Medicine Shops and Model Pharmacies in Dhaka Metropolis - Mst Marium Begum; Sanzana Fareen Rivu; Md. Ziauddin Iqbal; Nuzhat Tabassum; Nurnahar; Md. Sahab Uddin; Md. Marufur Rahman Moni; Md. Mahmud Al Hasan; Md. Sohanur Rahman (Hindawi Limited, 2021)
Model pharmacy has been adopted recently to upgrade the healthcare delivery system in Bangladesh. This study was aimed to analyze and compare the effectiveness of drug dispensing patterns, practices, and knowledge of both clients and dispensers of model pharmacies over traditional retail medicine shops. Two established methods, namely, client simulated method (CSM) and provider interview method (PIM), were employed to determine the practice differences in 90 retail medicine shops and 90 model pharmacies in and around Dhaka city. The results are represented primarily in comparison with corresponding percentages. The survey results did not fully support the findings obtained from the observations of the CSM as PIM contrasted these to some extent, and the differences are statistically significant (p<0.0001). According to CSM, the presence of A-grade pharmacists during working hours in retail medicine shops was 0%, and 63% in model pharmacies. As reported by PIM, in the retail medicine shops, 36% of clients were ignorant of visiting doctors before purchasing medicine. On the other hand, only 18% of clients could visit doctors. As per CSM, 40% of clients did not follow doctors' recommendations for completion of the full dose of antibiotics bought from retail medicine shops and 51% did not finish full antibiotic courses collected from model pharmacies. Additionally, CSM revealed that 28% of the clients administered leftover drugs following old and obsolete prescriptions of retail medicine shops and 21% of clients followed the same practices in terms of model pharmacies. The report of CSM revealed that 95% of dispensers of retail medicine shops sold medicine without prescription except over-the-counter (OTC), and in the model pharmacies, the percentage was 77%. The qualitative findings revealed substandard practices and dispensing pattern too. Model pharmacies were established to prevent aberrant medicine dispensing patterns and ensure proper medication dispensing practices and medicine intake. This research could not verify the situation that pharmacists or owners of model pharmacies were fully abiding by the guidelines set for them by the Directorate General of Drug Administration (DGDA).